Neutrophils Isolated from Septic Patients Exhibit Elevated Uptake of Vitamin C and Normal Intracellular Concentrations despite a Low Vitamin C Milieu - Anitra C. Carr; Stephanie Bozonet; Juliet Pullar; Emma Spencer; Patrice Rosengrave; Geoff Shaw (MDPI AG, 2021)
Vitamin C (ascorbate) plays an important role in neutrophil function and is accumulated by the cells either directly via vitamin C transporters (SVCT) or indirectly following oxidation to dehydroascorbic acid. Septic patients are known to have significantly depleted plasma ascorbate status, but little is known about the ascorbate content of their circulating cells. Therefore, we assessed the ascorbate concentrations of plasma, leukocytes and erythrocytes from septic patients and compared these to healthy controls. Non-fasting blood samples were collected from healthy volunteers (n = 20) and critically ill patients with sepsis (n = 18). The ascorbate content of the plasma and isolated neutrophils and erythrocytes was measured using HPLC and plasma myeloperoxidase concentrations were determined using ELISA. Ex vivo uptake of ascorbate and dehydroascorbic acid by neutrophils from septic patients was also assessed. Neutrophils isolated from septic patients had comparable intracellular ascorbate content to healthy volunteers (0.33 vs. 0.35 nmol/106 cells, p > 0.05), despite significantly lower plasma concentrations than the healthy controls (14 vs. 88 µmol/L, p < 0.001). In contrast, erythrocytes from septic patients had significantly lower intracellular ascorbate content than healthy controls (30 vs. 69 µmol/L, p = 0.002), although this was 2.2-fold higher than the matched plasma concentrations in the patients (p = 0.008). Higher concentrations of myeloperoxidase, a source of reactive oxygen species, were observed in the septic patients relative to healthy controls (194 vs. 14 mg/mL, p < 0.0001). In contrast to neutrophils from healthy volunteers, the neutrophils from septic patients demonstrated elevated uptake of extracellular ascorbate. Overall, neutrophils from septic patients exhibited comparable intracellular ascorbate content to those from healthy controls, despite the patients presenting with hypovitaminosis C. The mechanisms involved are currently uncertain, but could include increased generation of dehydroascorbic acid in septic patients, enhanced basal activation of their neutrophils or upregulation of their vitamin C transporters.